Governing urban regeneration in the UK: a case of 'variegated neoliberalism' in action?. Issue 6 (3rd June 2019) - Atkinson, Rob; Tallon, Andrew; Williams, David
ABSTRACT: The article focuses on the redevelopment of previously developed land by public-private sector partnerships in three cities/towns in South-West England, two of which can be described as medium-sized places with little previous experience of such developments. In each case we situated the redevelopment process in its wider multi-level and horizontal relationships using Social Network Analysis to produce network and centrality maps to reveal the complex network of relationships the process was embedded within and shaped by. These developments took place in what is termed the 'roll-out' phase of neoliberalism and we illustrate how the overarching planning and regulatory regimes (including contracts), along with wider economic conditions, shaped the development process, with the proviso that in each case these factors were mediated and themselves shaped by the assortment and interaction of local organizational, political, economic and civic forces. These included local planning committees and their interpretation of planning regulations and the developers involved, but also opposition to the developments from local sources. Much, however, depended on the 'capacity to act' of the relevant partnerships, in the sense of mobilizing and deploying available resources to realize the proposed developments.